Co-opting the Night: The Entrepreneurial Shift and Economic Imperative in NTE Planning. Issue 4 (2nd October 2017) - Wolifson, Peta; Drozdzewski, Danielle
Abstract: The City of Sydney Council has presented their night-time economy plan (NTE) – Open, Future directions for Sydney at night – as a unique and substantial contribution to global city planning literature. This paper critiques the plan and demonstrates how Open is strongly aligned with, and constrained by the neoliberal-inspired cultural-economy framework of the Council's overarching policy vision: Sustainable Sydney 2030 . Such co-opting of policy evinces an entrepreneurial shift in NTE planning where economic interests procure substantial voice in the consultation, and eventual policy directions of changing the nightscape. The paper explicates the economic imperative(s) of Open within the context of one inner city Sydney suburb, Surry Hills.